2000
DOI: 10.1017/s0714980800012460
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic Status and Self-Rated Health Among Older Canadians

Abstract: Although previous research has examined the various correlates of self-rated health, little attention has been paid to how position in the social structure influences this important measure of health. Drawing upon the social structure and personality perspective, I examine whether the relationship between socio-economic status (income adequacy and education) and self-rated health is mediated by financial stress, self-esteem, mastery, social support, smoking, alcohol consumption and physical activity, using dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 56 publications
(70 reference statements)
1
20
0
Order By: Relevance
“…Subjective income status is an integral aspect of one’s economic well-being because it can improve one’s assessment of one’s capacity to meet financial needs, including maintaining independent community-based living [44]. Perceived income adequacy has been reported in the literature in various ways and has been verified as a predictor of other outcome measures such as self-rated health [45], life satisfaction [46], and depressive symptoms [47]. …”
Section: Discussionmentioning
confidence: 99%
“…Subjective income status is an integral aspect of one’s economic well-being because it can improve one’s assessment of one’s capacity to meet financial needs, including maintaining independent community-based living [44]. Perceived income adequacy has been reported in the literature in various ways and has been verified as a predictor of other outcome measures such as self-rated health [45], life satisfaction [46], and depressive symptoms [47]. …”
Section: Discussionmentioning
confidence: 99%
“…The implication of this is that there is potential for further compressing morbidity and disability among entire cohorts, and not just the wealthiest within cohorts. Research shows that the relationship between SES and health is weakened when controls for material, lifestyle, and psychosocial resources are introduced (e.g., Cairney, 2000;Lantz, et al, 2001;McDonough et al, 2002), revealing that SES per se is not likely at the core of successful aging. Instead, these resources act as a conduit through which SES influences health (Denton & Walters, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Despite universal access to essential health care in Canada, research shows that socio-economic status (SES) is closely linked to health status among both younger and older adults (e.g., Cairney, 2000;Cairney & Arnold, 1996;Cairney & Arnold, 1998;Hay, 1988;Hirdes & Forbes, 1989;Hirdes et al, 1986;Mustard et al, 1997;Wilkins et al, 1991;Wolfson et al, 1993). Canadians with higher SES, especially well-educated and higher-income persons, have lower rates of morbidity and mortality than those with lower status.…”
Section: Introduction: the Socio-economic Stratification Of Healthmentioning
confidence: 99%
“…Yet it has been reported that positive indicators of psychological well-being such as life satisfaction (Lee and Shinkai 2003), perception of control (Chipperfield et al 2004), and self-esteem (Cairney 2000;Starr et al 2003), are also associated with subjective health. In fact, emerging evidence suggests that positive psychological functioning may represent an important long-term predictor of subjective health (Benyamini et al 2000).…”
mentioning
confidence: 99%